Counseling Fitness (COUNSFIT) Education in Enhancing Ideal Body Self-Imagery among Children with Autism - Auliya Assyifa; Hadi Pranoto; Tri Anjar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aimed to examine the effectiveness of Counseling Fitness (COUNSFIT) in improving self-imagery body ideal among children with autism by combining quantitative and qualitative approaches. The quantitative approach measured the percentage increase in scores before and after the intervention, while the qualitative approach described the process and behavioral changes during the program. The quantitative design used a pre-test, post-test, control-group design involving participants from an autism care community. The instrument was a validated self-imagery body ideal scale, while qualitative data were collected through structured observations and in-depth interviews. Quantitative data were analyzed using paired sample t-tests and percentage gain calculations, whereas qualitative data were analyzed thematically. The findings revealed a significant 32% increase in the experimental group compared to the control (p < 0.05). Children also demonstrated higher self-confidence, active participation, and a more positive body perception. This study recommends COUNSFIT as a feasible service model in inclusive schools and special needs intervention centers. Keywords: counseling fitness, self-imagery body ideal, counseling intervention, body image